2013
DOI: 10.1016/j.jnutbio.2012.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Citrullus lanatus ‘sentinel’ (watermelon) extract reduces atherosclerosis in LDL receptor-deficient mice

Abstract: Watermelon (Citrullus lanatus or C. lanatus) has many potentially bioactive compounds including citrulline, which may influence atherosclerosis. In this study, we determined the effects of C. lanatus, provided as an extract of the cultivar `sentinel', on hypercholesterolemia-induced atherosclerosis in mice. Male LDL receptor deficient mice at 8 weeks old were given either C. lanatus `sentinel' extract (2% vol/vol; n=10) or a mixture of matching carbohydrates (2% vol/vol; n=8) as the control in drinking water, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Chronic ingestion of watermelon extract has shown promise for reducing total and LDL-cholesterol concentrations in both mice (87) and younger adult subjects (88). Two research groups have reported beneficial effects of powdered watermelon extract on blood pressure and other measures of vascular function among adults with pre-existing obesity, prehypertension or stage 1 hypertension (Table 3) (46, 47, 4951).…”
Section: Discussionmentioning
confidence: 99%
“…Chronic ingestion of watermelon extract has shown promise for reducing total and LDL-cholesterol concentrations in both mice (87) and younger adult subjects (88). Two research groups have reported beneficial effects of powdered watermelon extract on blood pressure and other measures of vascular function among adults with pre-existing obesity, prehypertension or stage 1 hypertension (Table 3) (46, 47, 4951).…”
Section: Discussionmentioning
confidence: 99%
“…The rind of watermelon is usually green in color but may vary depending on the specie [5]. The rind make up the outer part of the fruit that cover the inner fleshy and commonly edible part usually composed of seeds [6]. In countries like Nigeria and some other parts of west Africa, the only part regarded as edible is the reddish inner fleshy part of the fruit [7].…”
Section: Introductionmentioning
confidence: 99%
“…Figueroa et al [4] demonstrated that watermelon juice supplementation improves aortic hemodynamics by reducing the reflected wave amplitude in prehypertensive individuals. A study by Poduri et al [5] reported that watermelon attenuated hypercholesterolemia-induced atherosclerosis in mice. Commercial watermelon juices provide enormous marketing potential and nutritious drinks for individuals to maintain a healthy lifestyle.…”
Section: Introductionmentioning
confidence: 99%